High Prevalence of Caesarian Sections at a Referral Hospital in Bangladesh - Bhuiya, Abdul Latif (Ibrahim Medical College Journal, 2009)
The rate of Caesarean delivery in Bangladesh is not known but thought to have increased markedly in recent years. This observational study addressed the prevalence of various types of deliveries conducted on 2714 subjects attending the postnatal ward of a referral hospital in Dhaka from August 1994 to March 1995. During this period data were collected retrospectively from their registries and clinical history sheets. Of these participants 1509 (55.6%) had a history of normal delivery and 1150 (42.4%) underwent Caesarean sections. Very few (1.7%) had other means of delivery and only 0.7% were reported to have forceps delivery. The Caesarian delivery for the first baby was 14.1%, which gradually decreased in subsequent deliveries. Most of the deliveries, be it normal or Caesarean, were conducted by the trainee doctors (43.6%) and Medical Officers (25.7%). Professors and Assistant Professors performed less than 1%. The normal or Caesarean deliveries were assisted mostly by trainee doctors (54.4%), interns (19.0%) and nurses (15.8%); and very few were conducted by Medical Officers (8.3%) and Assistant Registrars (2.1%). The study observes that the rate of Caesarean delivery is much higher than that observed in western countries. Most of the deliveries in this hospital, whether normal or Caesarean, were found to be conducted by the trainee or junior doctors. Ibrahim Med. Coll. J. 2009; 3(1): 21-23 Keywords: Pregnancy, normal delivery, Caesarean delivery, delivery practices, tertiary hospital. doi: 10.3329/imcj.v3i1.2915